Implementation of Internet based remote control and monitoring - Al-Khateeb, Khalid A. Saeed; Al-Khateeb, Wajdi Fawzi Mohammed; Hameed, Shihab A. (2009)
Remote monitoring and control of a multi-unit industrial facility can be achieved by utilizing the Internet. Electrical, mechanical and a variety of devices are switched on, off, and regulated from distant terminals. Commercially available components were used to build the system. Various aspects related to the method of access, security, standards, and current trends are discussed. An eight unit system has been implemented and tested. The system proved to be effective and easy to operate with a user friendly program, which can be readily adapted to deal with 256 units simultaneously. The wiring is reduced by using the ordinary power lines of the building to convey messages to and from the respective units. The system is also suitable for implementation by security and SCADA systems.